2005
DOI: 10.1007/s11244-005-2538-9
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of halogenated organic compounds in ground water by heterogeneous catalytic oxidation with hydrogen peroxide

Abstract: Catalytic oxidation with hydrogen peroxide is a reliable method for the treatment of polluted water. The conversion of a wide spectrum of components including aliphatic and aromatic hydrocarbons as well as halogenated organic compounds into non-toxic or minor-toxic substances and finally into carbon dioxide and water can be achieved. The degradation of chlorobenzene, 4-chlorophenol, 4-chloroaniline and 1-nitro-4-chlorobenzene was investigated. Several catalysts can be implemented into the catalytic process. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Among these techniques, catalytic wet peroxide oxidation (CWPO) appears to be a promising field of study. It has been reported to be effective for the near ambient degradation of soluble organic pollutants, because it can provide a nearly complete degradation (Garrido-Ramírez et al, 2010;Hofmann et al, 2005;Liotta et al, 2009;Meunier, 2002;Perathoner and Centi, 2005;Zrnčević and Gomzi, 2005). Active, economical and stable catalysts would play a critical role in the degradation of organic pollutants in CWPO.…”
Section: Introductionmentioning
confidence: 99%
“…Among these techniques, catalytic wet peroxide oxidation (CWPO) appears to be a promising field of study. It has been reported to be effective for the near ambient degradation of soluble organic pollutants, because it can provide a nearly complete degradation (Garrido-Ramírez et al, 2010;Hofmann et al, 2005;Liotta et al, 2009;Meunier, 2002;Perathoner and Centi, 2005;Zrnčević and Gomzi, 2005). Active, economical and stable catalysts would play a critical role in the degradation of organic pollutants in CWPO.…”
Section: Introductionmentioning
confidence: 99%
“…Various abatement techniques including biological, thermal, and chemical treatments have been developed in the last few years for the detoxification of organic pollutants [2,3]. Among these techniques, catalytic wet peroxide oxidation (CWPO) appears to be a promising field of study, which has been reported to be effective for the near ambient degradation of soluble organic pollutants, because it can provide a nearly complete degradation [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Hofmann et al [13] studied the degradation of chlorobenzene, 4-chlorophenol, 4-chloroaniline and pCNB in ground water by heterogeneous catalytic oxidation with hydrogen peroxide. It had been demonstrated that the type of catalyst and oxidation agent as well as the reaction parameters affected the degradation rate.…”
Section: Introductionmentioning
confidence: 99%